1996
DOI: 10.1210/jcem.81.6.8964833
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and tolerability of slow release lanreotide treatment in active acromegaly: six-month report on an Italian multicenter study. Italian Multicenter Slow Release Lanreotide Study Group.

Abstract: The objective of the study was to determine the tolerability and effectiveness of the slow release (SR) somatostatin analog lanreotide in active acromegaly. Fifty-seven patients, unselected in terms of their previous responsiveness to octreotide therapy, were included in a prospective, open label study carried out at 6 Italian endocrinological centers. The effects of 6 months of SR lanreotide, given at first every 14 days at a dosage of 30 mg, im, were recorded. In some patients (33%), drug dosage was adjusted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
33
0
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 41 publications
6
33
0
1
Order By: Relevance
“…In agreement with other trials with lanreotide SR (16,22,25), we observed a small rise in fasting blood glucose during therapy, whereas others found no change in glucose metabolism (23). In our study, as well as in others (22,23), no obvious deterioration in glucose metabolism was seen in patients with overt diabetes.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with other trials with lanreotide SR (16,22,25), we observed a small rise in fasting blood glucose during therapy, whereas others found no change in glucose metabolism (23). In our study, as well as in others (22,23), no obvious deterioration in glucose metabolism was seen in patients with overt diabetes.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, as well as in others (22,23), no obvious deterioration in glucose metabolism was seen in patients with overt diabetes.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Since the baseline IGF-I status did not influence the outcome of mean GH levels, we suggest that L-Autogel treatment can control clinical symptoms of acromegaly irrespective of GH levels. This has indeed been previously reported for lanreotide SR (8,35) and for octreotide LAR (23,24). Interpretation of our data is, however, limited by the nature of our open, one-way protocol.…”
Section: Discussionsupporting
confidence: 85%
“…a Frequencies are adopted from: octreotide LAR: http://www.rxlist.com according to manufacturer reports Cozzi et al, 2003;Davies et al, 1998;Flogstad et al, 1997;Jallad et al, 2005;Lancranjan and Atkinson, 1999;Lancranjan et al, 1996;Stewart et al, 1995); lanreotide autogel: Caron et al, 2002Caron et al, , 2006Lucas and Astorga, 2006); lanreotide SR: Attanasio et al, 2003;Caron et al, 1997;Chanson et al, 2000a,b;Giusti et al, 1996;Gutt et al, 2005;Lucas et al, 2003;Marek et al, 1994;Morange et al, 1994;Verhelst et al, 2000).…”
mentioning
confidence: 99%